The effect of type 2 diabetes on periapical osteoclast-related factors during axial tooth movement - Shi, Jing; Lin, Tong; Shi, Ziqing; Zhao, Jiaoyang; An, Xingqi; Xu, Yao; Zhu, Li; Li, Wenjin (Frontiers in Endocrinology, 2025)
ObjectivesTo explore the impact of type 2 diabetes on tooth axial elongation and its relationship with osteoclast-related factors.Materials and methodsWe established an unopposed molars model of type 2 diabetic mice, and recorded changes in mandibular bone mineral density (BMD) using micro-CT. Changes in the cells and fibers were observed by Hematoxylin and Eosin (HE) staining, Masson staining and Tartrate Resistant Acid Phosphatase (TRAP) activity assay of the right mandibles. The expression levels of osteopontin (OPN), receptor activator for nuclear factor-κ (RANK) and Receptor Activator of Nuclear Factor-κ B Ligand (RANKL) were observed using immunohistochemistry and RT-qPCR.ResultsMicro-computed tomography (CT) analysis showed that tooth elongation and bone mineral density (BMD) in both groups increased over time but were consistently lower in diabetic mice compared to controls. Histological staining showed that diabetic mice had more osteoclasts and bone resorption, with sparser collagen. Immunohistochemistry and RT-qPCR showed that the expression levels of osteopontin (OPN), receptor activator for nuclear factor-κ (RANK), and receptor activator of nuclear factor-κ B ligand (RANKL) in both groups increased over time but were higher in diabetic mice compared to controls.ConclusionsType 2 diabetes may slow down the axial elongation of teeth. The aggravate bone resorption based on the abnormal expression of RANK, RANKL, and OPN was a probable reason for the inhibition of alveolar bone remodeling.